Research Progress in the Efficacy and Safety of ALK Inhibitors in the Treatment of NSCLC Brain Metastasis - Yuchen CHEN; Han HAN; Jinpan WEI; Qianyu DU; Xiyong WANG (Chinese Journal of Lung Cancer, 2023)
Lung cancer is one of the most lethal malignancies in the world, with non-small cell lung cancer (NSCLC) accounting for approximately 80%-85% of all pathological types. Approximately 30%-55% of NSCLC patients develop brain metastases. It has been reported that 5%-6% of patients with brain metastases harbor anaplastic lymphoma kinase (ALK) fusion. ALK-positive NSCLC patients have shown significant therapeutic benefits after treatment with ALK inhibitors. Over the past decade, ALK inhibitors have rapidly evolved and now exist in three generations: first-generation drugs such as Crizotinib; second-generation drugs including Alectinib, Brigatinib, Ceritinib, and Ensartinib; and third-generation drugs like Lorlatinib. These drugs have exhibited varying efficacy in treating brain metastases in ALK-positive NSCLC patients. However, the numerous options available for ALK inhibition present a challenge for clinical decision-making. Therefore, this review aims to provide clinical guidance by summarizing the efficacy and safety of ALK inhibitors in treating NSCLC brain metastases.